Abdominal Pain Associated With Anorexia Nervosa and Median Arcuate Ligament Syndrome: A Rare Condition Shadowed by a Postoperative Conversion Disorder. (August 2020) - Fox, Charles J.; Morton, Alex; Watters, Ashlie; Mehler, Philip S.
Median arcuate ligament syndrome (MALS) is an often discounted and vexing condition that may go unnoticed in a population of patients with complex comorbid conditions or those with poor psychiatric health. We report a unique case of a patient with anorexia nervosa in whom the successful operation for MALS was briefly complicated by a postoperative conversion disorder.